EVALUATION OF BIOMETRIC INDICATORS IN LAMAS (LAMA GLAMA) OF THE CH´ACCU AND K´ARA VARIETIES - Llacsa M., Javier (2007)
Ninety nine llamas K´aras and Ch´accus with their babies were selected at La Raya Research and Production Center of Altiplano National University, Puno, to evaluate the measures of thoracic perimeter (PT), thigh volume (VM) and rump area (ASG) in baby llamas as biometric indicators for body weight (PV) by multiple regression models, and correlations between these variables with udder size (length and width) of the mothers. These evaluations were done at 1st, 2nd and 3rd month of age. The calculations of VM and ASG were done through geometric figures of truncated cone and trapezium respectively, using the Autocad engineering software. The coefficients of determination increased from medium to high as baby llamas increased in age, and the highest value was found at the age of 7 (R2 = 76.3%) and 3 (R2 = 70.0%) for Ch´accus and K´aras respectively. The major effect came from PT in Ch´acus whereas in K´aras was from PT and ASG at 1st and 3rd month of age and VM at 7th month (p<0.05). The relationship in baby llamas between PV and biometric measurements were high, positive and significant, especially at 7 months of age. The relationships between udder size (length and width) and PV, ASG, VM and PT were low with the exception of K´aras at 7 months of age. In general, PV, VM, ASG and PT increased by 55, 53, 34 and 19% and 108, 90, 60 and 35% at 3 and 7 months of age respectively, and without significant differences between breeds. Changes in udder size from the 1st month of age until 3 and 7 months of age were minimum. The results suggested that PT, VM and ASG could be used as biometric indicators of PV in selecting llamas for meat production.